SUBJEK PETANI DALAM WACANA PEMBANGUNAN DI MANGGARAI - Venansius Haryanto (Journal of Governance, 2017)
This study aim to trace how development discourse consturct the subject as peasant in Manggarai-NTT. This study found two important things. On One Side, development and all its principles try to epresentate subject as peasant in certain manner. On the other side, there are resistance narratives of subject as peasant to the way of how system representing them in development. This study took place in Lembor-West Manggarai Regency of NTT Province, that supposedly known as granary of NTT and national. This study used the concept of relation of power, subject and discourse in post-structuralist lens as analytical framework